Concerted roles of LRRTM1 and SynCAM 1 in organizing prefrontal cortex synapses and cognitive functions - Karen Perez de Arce; Adema Ribic; Dhrubajyoti Chowdhury; Katherine Watters; Garth J. Thompson; Basavaraju G. Sanganahalli; Elizabeth T. C. Lippard; Astrid Rohlmann; Stephen M. Strittmatter; Markus Missler; Fahmeed Hyder; Thomas Biederer (Nature Communications, 2023)
LRRTM1 is a post synaptic adhesion protein, that promotes AMPA receptor mediated synaptic transmission. Here the authors show that LRRTM1 and the adhesion molecule SynCAM 1 act together to organize synapses in the prefrontal cortex with relevance for cognitive function in mice.